2017
DOI: 10.1111/jth.13556
|View full text |Cite
|
Sign up to set email alerts
|

Refrigerated platelets stored in whole blood up to 5 days adhere to thrombi formed during hemorrhagic hypotension in rats

Abstract: Essentials • In vivo function of platelets stored at various conditions was studied in normo-and hypotension. • Refrigerated platelets stored up to 5 days performed as well as those stored at room temperature. • Platelet adhesion and thrombus formation were higher in ruptured vessels of hemorrhaged animals. • In vivo data suggest that refrigerated platelets are hemo-statically effective during hypotension. Summary. Background: There is renewed interest in the therapeutic use of cold-stored platelets for bleedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 54 publications
3
28
0
Order By: Relevance
“…Viscoelastic properties as measured by TEG was present in the CSP group for the entire 21‐day storage period, with better MA than room temperature storage on Day 7. This superior clot strength has previously been documented by several studies . While the DCSP group did show some remaining function on Day 21, this was substantially worse than for the CSP group.…”
Section: Discussionsupporting
confidence: 81%
“…Viscoelastic properties as measured by TEG was present in the CSP group for the entire 21‐day storage period, with better MA than room temperature storage on Day 7. This superior clot strength has previously been documented by several studies . While the DCSP group did show some remaining function on Day 21, this was substantially worse than for the CSP group.…”
Section: Discussionsupporting
confidence: 81%
“…If bleeding time is around the range of 2–3 min, it suggests that the residual platelets that survived the initial clearance had sufficient time to participate in clot formation when active bleeding occurred, which was supported by immunohistochemistry that showed GFP + ‐platelets at the clot of the liver incision site under both conditions of sham and ATC. This is consistent with the recent paper showing that platelets derived from cold stored whole blood participate in clot formation at sites of microvascular injury by laser puncture observed by intra‐vital microscopy with actual quantification (Torres Filho et al , ).…”
Section: Discussionsupporting
confidence: 92%
“…10 As a result, PLTs may be transfused before contamination is ultimately detected. 10 Recently, our laboratory has demonstrated that cold storage (CS; 4-6 C) of PLTs prolongs shelf life for periods in excess of 14 days 12 and preserves both PLT viability and hemostatic function, [12][13][14][15][16][17][18] allowing adequate time to quarantine units for the requisite 7 days necessary for bacterial culture. However, a longstanding criticism of PLT CS is that while it is assumed that CS would prevent bacterial growth, to our knowledge, no specific evidence has been reported for PLT components prepared by current procedures.…”
mentioning
confidence: 99%